Kajian Bentuk dan Fungsi Silat Pangean di Desa Kota Baru Kecamatan Rakit Kulim Kabupaten Indragiri Hulu - Yahyar Erawati; Fatia Kurniati; Ferry Aidil Saputra (Universitas Negeri Medan, 2026)
Pangean Silat is a form of martial art that features self-defense movements. Pangean Silat plays an important role in various traditional ceremonies, especially in Kota Baru Village, Riau Province. Initially, Pangean Silat was only used indoors, but over time, it began to develop and was brought to Silat Village with the aim of being studied by many people. Today, it has become an integral part of the community's traditions and customs, including in processions, welcoming guests, welcoming brides, and Panggak Adat Yang. This research aims to find out the form of movement and function of Pangean Silat in the lives of the people of Kota Baru Village, Riau Province. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that Pangean silat in Kota Baru Village is not only a martial art, but also includes entertainment silat which has an important role in the Panggak Adat procession in Kota Baru Village. The form of Pangean silat performance can be seen from several elements such as clothing, accompanying music, audience, stage, and performers. This research is expected to contribute to the development of the study of local culture and traditions, as well as increase awareness of the importance of this.